‘COUNSELLING: A PREREQUISITE TO IMPROVE QUALITY OF LIFE OF HIV POSITIVE WOMEN’ - et. al., Shirin Shikalgar (International Journal of Modern Agriculture, 2021)
Background: Globally, proportion of HIV positive women is higher compared to men (WHO, 2019), so is the socio-economic burden women experience. An effective way to mitigate this burden is by creating opportunities for women. More than 40% of people living with HIV infection in India are women. Experiences of HIV are different in men and women. Methods: A mixed method research design was employed. The study included quantitative survey of 147 HIV positive women in Maharashtra. Qualitative component included ten in depth interviews with the stakeholders providing legal, medical and psychological services. Qualitative data was analysed thematically, whereas, quantitative data was analysed using non-parametric test. Findings: Findings of the study show that education improves knowledge and contributes to empowerment. This study confirms the assertion made through quantitative findings that systemic support structures and empowerment of women need to be integral part of counselling and counsellors certainly has bigger role to play in it. Conclusion: For Healthy and dignified life HIV positive women need support of counsellors. Four areas of counselling have been emerged through this study- Legal and Right based counselling, family counselling, counselling on awareness of disease and psychological counselling. These four areas are vital to empower HIV positive women to lead a dignified life with care and support